Seven new Myrtaceae from Amazonian Brazil - Souza, Maria Anália Duarte De; Sobral, Marcos; Caldas, Diana K.d. (Phytotaxa, 2025)
Eugenia pseudoomissa, Myrcia acreana, Myrcia aripuanana, Myrcia viaria, Plinia acreana, P. amazonica and P. impressa, from Amazonian Brazil, are described and illustrated. Eugenia pseudoomissa is morphologically related to E. omissa, but differs by its glabrous condition and larger fruits; Myrcia acreana seems related to M. curtipendula, but differs by its shorter, not branched inflorescences; M. aripuanana is morphologically related to M. grazielae, but differs by the blades not bullate, shorter inflorescences and smaller flowers; M. viaria seems related to M. megapaniculata, but has larger leaves and non-apiculate calyptras; Plinia acreana reminds P. rogersiana, but differs by the blades with a higher number of lateral veins and more developed axes of inflorescences; P. amazonica seems related to P. cerrocampanensis, but differs by its sparse indumentum and smaller fruits, and P. impressa seems related to P. moralesii, but differs by its glabrous condition, wider blades with midvein adaxially impressed and oblate fruits. Additionally, conservation issues are discussed for each species.